Design comparison of hybrid masonry types for seismic lateral force resistance for low-rise buildings - Stallbaumer, Cassandra (Kansas State University, 2016)
The term hybrid masonry describes three variations of a lateral force resisting system that utilizes masonry panels inside steel framing to resist lateral loads from wind or earthquakes. The system originates from the rich history of masonry in the construction industry and is currently used in low-rise, low-seismic, wind-governed locations within the United States. Considerable research is focused on hybrid systems to prove their validity in high-seismic applications. The three variations of hybrid masonry are known by number. Type I hybrid masonry utilizes the masonry panel as a non-load-bearing masonry shear wall. Shear loads from the diaphragm are transferred into the beam, through metal plates, and over an air gap to the top of the masonry panel. The masonry panel transfers the shear to the beam below the panel using compression at the toe of the wall and tension through the reinforcement that is welded to the beam supporting the masonry. Steel framing in this system is designed to resist all gravity loads and effects from the shear wall. Type II hybrid masonry utilizes the masonry as a load-bearing masonry shear wall. The masonry wall, which is constructed from the ground up, supports the floor live loads and dead load of the wall, as well as the lateral seismic load. Shear is transferred from the diaphragm to the steel beam and into the attached masonry panel via shear studs. The masonry panel transfers the seismic load using compression at the toe and opposite corner of the panel. Type III hybrid masonry also utilizes the masonry panel as a load-bearing masonry shear wall, but the load transfer mechanisms are more complicated since the panel is attached to the surrounding steel framing on all four sides of the panel. This study created standard building designs for hybrid systems and a standard moment frame system with masonry infill in order to evaluate the validity of Type I and II hybrid masonry. The hybrid systems were compared to the standard of a moment frame system based on constructability, design, and economics.
Keywords: Hybrid masonry; Masonry; Seismic